Reliability, dead-time, and feasibility analysis of a novel modular tankless ZCS inverter for more electric aircraft - Mohd Tariq (2020)
An increase in the demand of the electrical power in the more electric aircraft (MEA) with electrical equipment replacing the pneumatic and hydraulic equipment; the modular power converter (MPC) is needed for power conversion and power distribution in the MEA. The MPC is a promising technological solution for high voltage and high power conversion. The scalable configuration of MPC's improves reliability and availability of the converter. This paper presents a novel modular zero current switching (ZCS) inverter for applications in the MEA. The proposed inverter achieves ZCS through a modular circuital configuration and eliminates the utilization of dead time. Elimination of dead time in the proposed topology will be helpful in proposing a low-complex control circuit for its integration with the 270-V dc power distribution architecture of the MEA. Moreover, with respect to MEA, the reliability and economic feasibility of the converter is also important, as reliability is a fundamental requirement in aircraft safety-critical equipment. A comparative analysis in terms of reliability, economic feasibility, and the effect of dead time on inverter output for the proposed inverter with respect to the conventional pulsewidth modulated inverter is presented in this paper. The operational and low loss features of the proposed converter are highlighted.